The Analysis of Struck-By Accidents at Construction Sites in Johor - Abas, Nor Haslinda (International Journal of Integrated Engineering, 2020)
Construction industry plays an essential role in raising Malaysia’s economic growth. Despite the importance of this sector, it is also has been categorized as the most hazardous industry due to its high risk in causing construction accidents compared to the other industry. Among the various reported accident fatality cases to the Department of Occupational Safety and Health (DOSH) from year 2010 to 2018, the struck-by object accident is among of the Top 3 most contributed fatal accident types. Therefore, this study aims is to investigate the significant contributing factors of this type of accident. The study was carried out by obtaining the cases of fatal accidents due to struck-by object accidents that was happened in Johor construction industry from DOSH website. The contributing factors to struck-by object accidents was computed from the real cases and literature review, and later designed as the questionnaire to distribute to the respondents that comprises of safety personnel working at construction sites. About 116 answered questionnaires were analysed and the results of Relative Importance Index (RII) were compared with the real cases. From the questionnaire survey, the most significant contributing factor to struck-by object accidents is due to lack of training. Whereas for the analysis on the real cases, the significant contributing factor to struck-by object accidents is no safe operating procedure. There exists a variation in the respondents’ perceptions with the real cases as shown by Spearman’s rank correlation. This study provides awareness to the construction practitioners to minimize the rate of struck-by object accidents by implementing the effective measure to the hidden factor of accident.